AN INTEGRATIVE MODEL OF EMOTIONAL INTELLIGENCE, PSYCHOLOGICAL CAPITAL, PROACTIVE PERSONALITY, WORK ENGAGEMENT AND JOB PERFORMANCE - Zahra, Munazza Zahra; Mui Kee Hung, Daisy Mui Kee Hung (Journal of Human Capital Development (JHCD), 2021)
Abstract. The workplace is increasingly becoming a setting where continued existence requires an above-average performance of the employees. A competitive advantage can no longer be obtained simply by increasing widespread technologies. By the same way, success can no longer be obtained by merely attempting to correct flaws of human resources. The pre-requisite of today’s workplace is to understand the importance of human strengths rather than focusing on “fixing the flaws” paradigm. Therefore, the prime objective of this research is to propose an integrative model to study the impact of the positive strengths of employees on job performance. The present study used two different research approaches to get maximum possible relevant studies related to positive organizational behaviour criteria. First, electronic databases and secondly indexed journals related to psychology, human resource management and organisational behaviour. An integrative model has been proposed linking emotional intelligence, psychological capital, and proactive personality to job performance via work engagement. The research argues that human strengths such as emotional intelligence, psychological capital, proactive personality, and work engagement are essential factors that can play a significant role in enhancing job performance of the employees. Based on JDR perspective, coupled with the positive organizational behaviour theory, the researchers propose a novel framework pertinent to the banking sector of Pakistan. The conceptual framework has not yet been tested empirically. Hence, future studies are necessary to empirically test the framework using survey. Keywords: Emotional intelligence; Psychological capital; Proactive Personality; Job Performance; Work engagement